Hip-Fracture Care in Rural Southwestern Ontario: An Ethnographic Study of Patient Transitions and Physiotherapy Handoffs - Johnson, Helen (University of Toronto Press Incorporated, 2013)
Purpose: To examine information exchange by physiotherapists during care handoffs of patients with hip fracture in a rural health care setting. Methods: This qualitative ethnographic study used observation and interviews of 11 networks of patients with hip fracture (n=11), family caregivers (n=8), and health care providers (n=24). Patients were followed from acute care through each subsequent care setting. Data were supplemented by health care records and policy documents. Results: Findings revealed that handoffs were less successful when information transfer was untimely or incomplete. Family caregivers experienced challenges in obtaining information required to facilitate the handoff, especially when direct contact with physiotherapists was not possible as a result of distance or other factors. Physiotherapists had to navigate multiple data sources to retrieve important information, and managed information gaps in various ways. Information flow was often unidirectional and suggested no further clinical accountability for the discharging physiotherapist. Conclusions: Providing information in a structured and timely fashion facilitated physiotherapy handoffs. Inadequate handoffs compromised continuity of care, delayed progress in rehabilitation, and resulted in families' missing information of vital importance to their caregiving role. A multi-directional exchange of information is needed between patients, families, and health care providers across care settings.